Influence of crack micro-roughness on the plasticity-induced fatigue propagation in high strength steel (Fracture and Structural Integrity, 2017)
This article deals with the locally multiaxial fatigue behaviour of high strength steel. To this end, the influence of the cracking path deflections (at the micro level) on the plasticity-induced fatigue crack growth is analyzed. With regard to this, a modelling by means of the finite element method was performed for a given stress intensity factor in the Paris regime, considering the existence of micro-roughness in the crack path (local micro-deflections with distinct micro-angles as a function of the microstructure of the material). The numerical results allow one to obtain the fatigue crack propagation rate and compare it with that for the same material in the absence of micro-roughness (with no micro-crack deflections, i.e., uniaxial fatigue behaviour).
Keywords: Crack tip; Micro-roughness; Crack deflection; Plasticity-induced fatigue crack propagation; Finite element method